A population-based cohort study of obesity, ethnicity and COVID-19 mortality in 12.6 million adults in England - Thomas Yates; Annabel Summerfield; Cameron Razieh; Amitava Banerjee; Yogini Chudasama; Melanie J. Davies; Clare Gillies; Nazrul Islam; Claire Lawson; Evgeny Mirkes; Francesco Zaccardi; Kamlesh Khunti; et al. (Nature Communications, 2022)
Obesity is a known risk factor for severe COVID-19 disease. Here, the authors use linked Census, electronic health records, and mortality data for 12.6 million adults in England and show that the association between COVID-19 mortality and body mass index is stronger in ethnic minority groups.